Adsorption sheet and manufacturing method thereof

By formulating an adsorbing sheet with a balanced content of inorganic and organic materials, including inorganic fibers, adsorbents, synthetic fibers, organic natural fibers, and a hot water-soluble resin, the sheet achieves both excellent flame retardancy and processability, addressing the trade-off issue in existing technologies.

JP7653504B2Active Publication Date: 2025-03-28TOMOEGAWA CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023217229
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-12-22
Publication Date
2025-03-28
Estimated Expiration
2040-01-20

AI Technical Summary

Technical Problem

Existing adsorbing sheets face a trade-off between flame retardancy and processability, making it difficult to achieve both properties simultaneously.

Method used

The adsorbing sheet is composed of inorganic fibers, inorganic adsorbents, synthetic fibers, organic natural fibers, and a hot water-soluble resin, with a specific mass content ratio of 84-92% inorganic matter and 8-16% organic matter, which enhances both flame retardancy and processability.

Benefits of technology

This composition allows for an adsorbing sheet with excellent flame retardancy and processability, making it suitable for use in desiccant rotors without compromising on either property.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007653504000001
    Figure 0007653504000001
  • Figure 0007653504000002
    Figure 0007653504000002
  • Figure 0007653504000003
    Figure 0007653504000003
Patent Text Reader

Abstract

To provide an adsorption sheet having excellent flame retardancy and workability and a method for producing the same.SOLUTION: A adsorption sheet has inorganic fiber, inorganic adsorbent, synthetic fiber, organic natural fiber, and a hot-water-soluble resin. The hot-water-soluble resin is attached to the organic natural fiber. Relative to the total mass of the adsorption sheet, the content of organic matter in the adsorption sheet is 8-16 mass%, and the content of inorganic matter in the adsorption sheet is 84-92 mass%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an adsorption sheet and a method for producing the same. [Background technology]

[0002] 2. Description of the Related Art Conventionally, adsorbent sheets that have excellent heat resistance and are capable of adsorbing and removing malodors of organic solvents and the like have been known. For example, Patent Document 1 discloses an adsorbent sheet that contains an adsorbent material, an organic component, and an inorganic binder, and that loses weight by 1% or less when heated in air at 300° C. for 30 minutes. Patent Document 2 describes an adsorbent and a fiber having a fiber diameter of 3.0 μm or less and a specific gravity of 3.0 g / cm 3 An adsorption sheet containing the following inorganic fibers and an organic binder has been disclosed. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 9-94422 [Patent Document 2] JP 2004-249259 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, the adsorption sheets described in the cited documents 1 and 2 do not necessarily have satisfactory processability. Therefore, for example, when the adsorption sheet is corrugated for a desiccant rotor constituting a desiccant air conditioner, cracks, breakage, etc. may occur. To improve the processability of the adsorption sheet, the proportion of inorganic matter in the adsorption sheet may be reduced and the proportion of organic matter may be increased, but the greater the proportion of organic matter, the lower the flame retardancy of the adsorption sheet tends to be. Conversely, to improve the flame retardancy of the adsorption sheet, the proportion of inorganic matter in the adsorption sheet may be increased and the proportion of organic matter may be reduced, but the smaller the proportion of organic matter, the lower the processability of the adsorption sheet tends to be. Thus, there is a trade-off between the flame retardancy and processability of the adsorption sheet, and it is difficult to achieve both flame retardancy and processability.

[0005] An object of the present invention is to provide an adsorbent sheet having excellent flame retardancy and processability, and a method for producing the same. [Means for solving the problem]

[0006] The present invention has the following aspects. [1] An adsorption sheet containing inorganic fibers, an inorganic adsorbent, synthetic fibers, organic natural fibers, and a hot water soluble resin, wherein the hot water soluble resin is adhered to the organic natural fibers, and the content of the organic matter contained in the adsorption sheet is 8 to 16 mass % and the content of the inorganic matter contained in the adsorption sheet is 84 to 92 mass % relative to the total mass of the adsorption sheet. [2] The adsorption sheet of [1], further containing a supporting auxiliary. [3] The adsorption sheet of [1] or [2], wherein the inorganic fiber is glass fiber. [4] The adsorption sheet of any one of [1] to [3], wherein the synthetic fiber is at least one of a polyethylene terephthalate fiber and a polyolefin fiber. [5] The adsorption sheet of any one of [1] to [4], wherein the organic natural fiber is at least one of wood pulp and straw pulp. [6] The adsorption sheet of any of [1] to [5], wherein the content of organic matter contained in the adsorption sheet is 10 to 14 mass % and the content of inorganic matter contained in the adsorption sheet is 86 to 90 mass % relative to the total mass of the adsorption sheet. [7] An adsorption sheet of any of [1] to [6] for use with a desiccant rotor. [8] The adsorption sheet according to [7], wherein the inorganic adsorbent is at least one of type A silica gel and zeolite. [9] A method for producing an adsorbent sheet according to any one of [1] to [8], comprising the steps of: disintegrating and dispersing the inorganic fibers, the synthetic fibers, and the hot water-soluble resin in water to obtain a first dispersion; dispersing the remaining materials in water to obtain a second dispersion; mixing the first dispersion and the second dispersion to obtain a papermaking slurry; papermaking the papermaking slurry using a papermaking machine to obtain a wet sheet having a water retention rate of 65 to 75 mass%; compressing the wet sheet so as to have a compression rate of 0 to 45% to obtain a compressed sheet; and drying the compressed sheet to dissolve the hot water-soluble resin and adhere it to the organic natural fibers.

[10] The method for producing an adsorption sheet according to [9], further comprising drying the compressed sheet at 70 to 180°C. Effect of the Invention

[0007] According to the present invention, it is possible to provide an adsorption sheet having excellent flame retardancy and processability, and a method for producing the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] "Adsorption sheet" The adsorption sheet of the present invention contains the following inorganic fibers, inorganic adsorbents, synthetic fibers, organic natural fibers, and hot water soluble resins. The adsorption sheet preferably further contains the following supporting aid.

[0009] <Inorganic fibers> The inorganic fibers are a component that imparts flame retardancy to the adsorption sheet. Examples of inorganic fibers include amorphous fibers such as glass fibers, glass wool, and rock wool fibers; polycrystalline fibers such as carbon fibers, activated carbon fibers, and alumina fibers; mineral fibers such as asbestos; and metal fibers such as stainless steel fibers and copper fibers. Among these, amorphous fibers are preferred from the viewpoint of cost, and glass fibers are more preferred from the viewpoint of increasing the strength of the adsorption sheet. These inorganic fibers may be used alone or in combination of two or more.

[0010] The average fiber length of the inorganic fibers is preferably 0.5 to 10 mm, more preferably 3 to 6 mm. If the average fiber length of the inorganic fibers is equal to or greater than the lower limit, the inorganic fibers will function as aggregates in the adsorption sheet, and are effective in ensuring sheet strength. If the average fiber length of the inorganic fibers is equal to or less than the upper limit, deterioration of the texture due to entanglement of the long fibers can be prevented. The average fiber length of inorganic fibers is the arithmetic mean of the longitudinal lengths of 20 inorganic fibers randomly selected under a microscope. If the inorganic fibers are not straight, the length is taken as the curved length along the fiber.

[0011] The average fiber diameter of the inorganic fibers is preferably 4.0 to 13.0 μm, more preferably 4.5 to 9.0 μm. If the average fiber diameter of the inorganic fibers is equal to or greater than the lower limit, the strength is favorable due to the aggregate effect and entanglement. If the average fiber diameter of the inorganic fibers is equal to or less than the upper limit, the number of fibers is sufficient, and as a result, the texture is prevented from becoming coarse. The average fiber diameter of the inorganic fibers is the arithmetic mean of the area diameters obtained by calculating the cross-sectional area perpendicular to the longitudinal direction of the inorganic fibers using a known calculation method based on vertical cross-sections at any 20 points of the adsorption sheet imaged with a microscope, and then calculating the diameter of a perfect circle having the same area as the cross-sectional area.

[0012] <Inorganic adsorbents> The inorganic adsorbent is a component that imparts to the adsorbent sheet the ability to adsorb and remove odors such as those of organic solvents, moisture, and the like. Examples of inorganic adsorbents include type A silica gel, type B silica gel, zeolite (including molecular sieve and HASClay), activated carbon, clay, etc. Among these, when the adsorption sheet is used for a desiccant rotor, type A silica gel and zeolite (such as molecular sieve or HASClay) are preferred, and type A silica gel is more preferred, from the viewpoint of excellent adsorption properties on the low humidity side required for an absorption sheet for a desiccant rotor. These inorganic adsorbents may be used alone or in combination of two or more.

[0013] <Synthetic fibers> The synthetic fibers are a component that enhances the tear strength and imparts processability to the adsorbent sheet. Examples of synthetic fibers include polyethylene terephthalate (PET) fibers, polyolefin fibers (e.g., polyethylene (PE) fibers, polypropylene (PP) fibers, etc.), acrylic fibers, etc. Among these, PET fibers and polyolefin fibers are preferred, and PET fibers are more preferred, from the viewpoint of the presence of core-sheath fibers having a core component that serves as an aggregate and a sheath component that serves as a binder. These synthetic fibers may be used alone or in combination of two or more.

[0014] The average fiber length of the synthetic fibers is preferably 0.5 to 10 mm, more preferably 3 to 6 mm. If the average fiber length of the synthetic fibers is equal to or greater than the lower limit, the synthetic fibers can exhibit the effect of further increasing the tear strength of the aggregate of the adsorption sheet. If the average fiber length of the synthetic fibers is equal to or less than the upper limit, deterioration of the texture due to entanglement of the long fibers can be prevented. The average fiber length of the synthetic fibers is determined in the same manner as the average fiber length of the inorganic fibers.

[0015] The average fiber diameter of the synthetic fibers is preferably 3 to 20 μm, and more preferably 9 to 13 μm. When the average fiber diameter of the synthetic fibers is equal to or greater than the lower limit, deterioration of flame retardancy due to an increase in the surface area of ​​the organic matter caused by an excessive number of fibers (i.e., an increase in gas generated during combustion) can be prevented. When the average fiber diameter of the synthetic fibers is equal to or less than the upper limit, reduction in strength and deterioration of texture due to an insufficient number of fibers can be prevented. The average fiber diameter of the synthetic fibers is determined in the same manner as the average fiber diameter of the inorganic fibers.

[0016] <Organic natural fibers> The organic natural fibers are a component that enhances processing strength and imparts processability to the adsorbent sheet. The organic natural fibers also serve as a carrier for supporting the inorganic adsorbent and as fibers to which the hot water soluble resin described below adheres. The organic natural fibers are preferably fibrillated in order to facilitate the support of the inorganic adsorbent.

[0017] Organic natural fibers include plant matter and animal matter. Examples of vegetable matter include wood pulp and natural fibers other than wood pulp (e.g., cotton, straw, bamboo, esparto, bagasse, linter, Manila hemp, flax, hemp, jute, gampi, etc.) In the present invention, semi-synthetic fibers such as acetate fiber and viscose rayon are also included in vegetable matter. Examples of animal materials include wool and silk. Among these, from the viewpoint of excellent hydrophilicity and dispersibility in water, those having a hydroxy group (OH group) are preferred, vegetable matter is more preferred, wood pulp and straw pulp are further preferred, and wood pulp is particularly preferred. These organic natural fibers may be used alone or in combination of two or more.

[0018] Examples of wood pulp include chemical pulps such as high-yield unbleached softwood kraft pulp (HNKP; N material), bleached softwood kraft pulp (NBKP; N material, NB material), unbleached hardwood kraft pulp (LUKP; L material), and bleached hardwood kraft pulp (LBKP, L material); mechanical pulps such as ground wood pulp (GP), pressure-risen ground wood pulp (PGW), and thermomechanical pulp (TMP); recycled paper pulp such as deinking pulp (DIP) and waste pulp (WP), and semi-chemical pulp (CP). These wood pulps may be used alone or in combination of two or more.

[0019] The average fiber length of the organic natural fibers is preferably 0.2 to 3.5 mm, more preferably 0.5 to 2.5 mm. If the average fiber length of the organic natural fibers is equal to or greater than the lower limit, the flocs formed in the second dispersion step described below do not become too small, and the amount of flocs that fall out of the wire during papermaking is reduced, thereby suppressing yield loss. If the average fiber length of the organic natural fibers is equal to or less than the upper limit, the flocs can be prevented from becoming too large. The average fiber length of the organic natural fibers is determined in the same manner as the average fiber length of the inorganic fibers.

[0020] The average fiber diameter of the organic natural fibers is preferably 10 to 30 μm, more preferably 15 to 25 μm. If the average fiber diameter of the organic natural fibers is equal to or greater than the lower limit, the flocs formed in the second dispersion step described below do not become too small, and the amount of flocs that are pulled out of the wire during papermaking is reduced, thereby suppressing yield loss. If the average fiber diameter of the organic natural fibers is equal to or less than the upper limit, the inorganic adsorbent is more easily supported due to improved physical support. The average fiber diameter of the organic natural fibers is determined in the same manner as the average fiber diameter of the inorganic fibers.

[0021] <Hot water soluble resin> The hot water soluble resin is attached to the organic natural fibers. The organic natural fibers are components with low heat resistance. In particular, fibrillated organic natural fibers have a large specific surface area and are prone to generating flammable gases when heated. As a result, the number of reaction sites between the gas and oxygen increases, making them more flammable. However, in the adsorption sheet of the present invention, since the hot water-soluble resin is attached to the organic natural fibers, it is believed that the combined specific surface area of ​​the hot water-soluble resin and the organic natural fibers is reduced due to the above-mentioned adhesion effect, and the instantaneous generation of the above-mentioned flammable gas during combustion is reduced, thereby improving the flame retardancy of the adsorption sheet. Although the reason why the heat resistance of the organic natural fibers is increased is not clear, it is believed that the attachment of the hot water-soluble resin to the organic natural fibers reduces the specific surface area of ​​the organic natural fibers, and as a result, the heat resistance of the organic natural fibers is increased. Furthermore, by adhering the hot water soluble resin to the organic natural fibers, the tensile strength of the adsorbent sheet is improved. In the present invention, "a hot water-soluble resin is adhered to an organic natural fiber" means that the hot water-soluble resin is adhered to the surface of the organic natural fiber and / or the organic natural fiber is impregnated with the hot water-soluble resin.

[0022] In the present invention, the term "hot water-soluble resin" refers to a resin that starts to dissolve in hot water of 60° C. or higher under normal pressure. Examples of such hot water-soluble resins include polyvinyl alcohol (PVA), ethylene-vinyl alcohol copolymer (EVOH), starch, etc. Among these, from the viewpoint of easy availability as a fibrous hot water-soluble resin, PVA and EVOH are preferred, and PVA is more preferred. These hot water soluble resins may be used alone or in combination of two or more. The synthetic fibers described above and the organic fine fibers described below are fibers that do not start to dissolve in hot water of 60° C. or higher under normal pressure.

[0023] <Supporting agent> The support aid is a component that enhances the supportability of the inorganic adsorbent on organic natural fibers. Examples of the support aid include fine fibers other than the above-mentioned inorganic fibers, synthetic fibers, organic natural fibers, and hot water-soluble resins. Examples of such fine fibers include inorganic fine fibers and organic fine fibers. Examples of inorganic fine fibers include potassium titanate fibers and single crystal fibers such as wollastonite. An example of the organic fine fibers is microfibril cellulose. Among these, from the viewpoint of further improving the flame retardancy of the adsorption sheet, inorganic fine fibers are preferred, and potassium titanate fibers are more preferred. These fine fibers may be used alone or in combination of two or more.

[0024] The average fiber length of the fine fibers is preferably less than 200 μm, more preferably 10 to 20 μm. When the average fiber length of the fine fibers is less than the upper limit, even when an inorganic adsorbent having a wide particle size distribution in which fine particles having a particle size of 1 μm or less are clearly present is used, the fine fibers become entangled when a polymer flocculant is added in the second dispersion step described later, thereby increasing the support rate and preventing a decrease in yield. The average fiber length of the fine fibers is a value determined in the same manner as the average fiber length of the inorganic fibers.

[0025] The average fiber diameter of the fine fibers is preferably less than 1 μm, more preferably 0.1 to 0.5 μm. When the average fiber diameter of the fine fibers is less than the upper limit, even when an inorganic adsorbent having a wide particle size distribution in which fine particles having a particle diameter of 1 μm or less are clearly present is used, the fine fibers become entangled when a polymer flocculant is added in the second dispersion step described later, thereby increasing the support rate and preventing a decrease in yield. The average fiber diameter of the fine fibers is a value determined in the same manner as the average fiber diameter of the inorganic fibers.

[0026] <Optional ingredients> The adsorption sheet may contain components (optional components) other than the inorganic fibers, inorganic adsorbents, synthetic fibers, organic natural fibers, hot water-soluble resins and supporting aids, so long as the effects of the present invention are not impaired. Examples of optional components include additives such as surfactants, dispersants, thickeners, defoamers, dry strength agents, and wet strength agents. These optional components may be used alone or in combination of two or more.

[0027] <Content> The content of the organic matter contained in the adsorption sheet is 8 to 16 mass %, and preferably 10 to 14 mass %, based on the total mass of the adsorption sheet. The content of the inorganic substance contained in the adsorption sheet is 84 to 92 mass %, and preferably 86 to 90 mass %, based on the total mass of the adsorption sheet. When the content of the organic substance is equal to or more than the lower limit and the content of the inorganic substance is equal to or less than the upper limit, the adsorption sheet has excellent processability.When the content of the organic substance is equal to or less than the upper limit and the content of the inorganic substance is equal to or more than the lower limit, the adsorption sheet has excellent flame retardancy. The organic matter contained in the adsorption sheet is synthetic fiber, organic natural fiber, hot water soluble resin, etc. When the adsorption sheet contains organic fine fiber as a support assistant, the organic fine fiber also falls under the category of organic matter. The inorganic substances contained in the adsorption sheet are inorganic fibers and inorganic adsorbents. When the adsorption sheet contains inorganic fine fibers as a support assistant, the inorganic fine fibers also fall under the category of inorganic substances. The content of inorganic matter contained in the adsorbent sheet is determined by burning the adsorbent sheet until all the organic matter contained in the adsorbent sheet is reduced to ash, removing the ash contained in the residue after combustion, measuring the mass of the remaining inorganic matter, and calculating the ratio of the mass of the inorganic matter to the mass of the adsorbent sheet before combustion as a percentage. The sum of the inorganic matter content and the organic matter content is 100% by mass. The amounts of materials used in the manufacture of the adsorption sheet generally coincide with the contents of inorganic and organic substances determined by the above method.

[0028] The content of the inorganic fibers is preferably 10 to 35 mass %, and more preferably 13 to 21 mass %, based on the total mass of the adsorption sheet. If the content of the inorganic fibers is equal to or more than the lower limit, the flame retardancy of the adsorption sheet is further improved, and if it is equal to or less than the upper limit, the processability of the adsorption sheet is further improved.

[0029] The content of the inorganic adsorbent is preferably 40 to 75 mass %, more preferably 50 to 70 mass %, based on the total mass of the adsorption sheet. If the content of the inorganic adsorbent is equal to or more than the lower limit, the adsorption properties of the adsorption sheet are sufficient, and if it is equal to or less than the upper limit, the processability of the adsorption sheet is further improved.

[0030] The synthetic fiber content is preferably 1 to 8 mass %, and more preferably 2 to 6 mass %, of the total mass of the adsorption sheet. If the synthetic fiber content is equal to or more than the lower limit, the processability of the adsorption sheet is improved, and if it is equal to or less than the upper limit, the flame retardancy of the adsorption sheet is improved.

[0031] The content of the organic natural fibers is preferably 2 to 10 mass % and more preferably 3 to 8 mass % based on the total mass of the adsorption sheet. When the content of the organic natural fibers is within the above range, the flame retardancy of the adsorption sheet is further improved. In particular, when the content of the organic natural fibers is equal to or greater than the lower limit, the processability of the adsorption sheet is further improved.

[0032] The content of the hot water-soluble resin is preferably 1 to 8 mass %, and more preferably 2 to 6 mass %, relative to the total mass of the adsorption sheet. If the content of the hot water-soluble resin is equal to or more than the above lower limit, the flame retardancy of the adsorption sheet is further improved, and if it is equal to or less than the above upper limit, adhesion to dryers and canvases during the manufacturing process of the adsorption sheet can be prevented.

[0033] The content of the supporting aid is preferably 3 to 20 mass % and more preferably 4 to 6 mass % based on the total mass of the adsorption sheet. If the content of the supporting aid is equal to or more than the lower limit, the supporting ability of the inorganic adsorbent to the organic natural fiber is improved. If the content of the supporting aid is equal to or less than the upper limit, the cost can be reduced.

[0034] <Thickness> The thickness of the adsorption sheet is preferably 150 to 300 μm, and more preferably 180 to 240 μm. The thickness of the suction sheet can be measured in accordance with JIS P 8118:1988 "Paper and paperboard -- Test methods for thickness and density."

[0035] <Manufacturing method> The adsorbent sheet can be produced by a wet papermaking method. An example of the method for producing the adsorbent sheet will be described below. The method for producing an adsorption sheet according to this embodiment includes the steps described below.

[0036] (First Dispersion Step) The first dispersion step is a step of disintegrating and dispersing the materials constituting the adsorption sheet, that is, inorganic fibers, synthetic fibers, hot water-soluble resin, and optional components as necessary, in water to obtain a first dispersion. The hot water-soluble resin may be in the form of fibers or in a form other than fibers (such as particles, pellets, powder, etc.). From the viewpoint of ease of papermaking, it is preferable to use a fibrous hot water-soluble resin.

[0037] The first dispersion can be obtained, for example, by adding inorganic fibers, synthetic fibers, a hot water-soluble resin, and optional components to water, and stirring and mixing the mixture to obtain a first dispersion in which the inorganic fibers, synthetic fibers, hot water-soluble resin, and optional components are dispersed in water. The water content of the first dispersion is preferably from 98.5 to 99.9 mass %, more preferably from 99.5 to 99.9 mass %, based on the total mass of the first dispersion.

[0038] (Second Dispersion Step) The second dispersion step is a step in which the remaining materials, that is, the materials constituting the adsorption sheet that were not used in the first dispersion step, are dispersed in water to obtain a second dispersion. Of the materials constituting the adsorbent sheet described above, the inorganic adsorbent and organic natural fibers, and, if necessary, a supporting aid and optional components, make up the remaining materials.

[0039] The second dispersion can be obtained, for example, by adding the inorganic adsorbent, the organic natural fibers, and, if necessary, at least one of the supporting aid and the optional components to water, and stirring and mixing the mixture to obtain a second dispersion in which the inorganic adsorbent, the organic natural fibers, and, if necessary, at least one of the supporting aid and the optional components are dispersed in water. The water content of the second dispersion is preferably from 95.0 to 99.5% by mass, and more preferably from 96.0 to 98.0% by mass, based on the total mass of the second dispersion.

[0040] For example, when there is a concern that A-type silica gel or the like may be altered in an alkaline environment, it is preferable to maintain the water quality of the second dispersion at pH 3.5 to 6.5, preferably pH 4.0 to 5.0. From this viewpoint, it is preferable to use the remaining material and an acid in combination. Specifically, it is preferable to add the remaining material and the acid to water and mix them by stirring. Examples of the acid include citric acid, sulfuric acid, hydrochloric acid, etc. Alternatively, a flocculant such as aluminum sulfate can be used as a substitute as long as it is within the above pH adjustment range.

[0041] It is also preferable to add the remaining materials and, if necessary, an acid to water, stir and mix, and then add a polymer flocculant. By adding the polymer flocculant, the inorganic adsorbent and the organic natural fibers flocculate to form flocculated flocs (aggregates). The formation of flocculated flocs makes it easier for the inorganic adsorbent to be held (supported) by the organic natural fibers. Examples of the polymer flocculant include cationic, anionic or nonionic polyacrylamides, sodium polyacrylates, polyacrylic acid esters, polymethacrylic acid esters, polyvinyl amidines, polydamodacs, polyamines, dicyandiamides, polyethyleneimines and the like.

[0042] (Slurry preparation process) The slurry preparation step is a step of mixing the first dispersion and the second dispersion to obtain a papermaking slurry. The method for mixing the first dispersion and the second dispersion is not particularly limited. The water content of the papermaking slurry is preferably 99.7 to 99.95 mass %, more preferably 99.9 to 99.94 mass %, based on the total mass of the papermaking slurry.

[0043] (Paper making process) The papermaking process is a process in which the papermaking slurry is made into a wet sheet having a water retention rate of 65 to 75% by mass using a papermaking machine. The papermaking machine is not particularly limited as long as it is a papermaking machine applicable to general papermaking techniques, and examples thereof include a Fourdrinier papermaking machine, a Short Wire papermaking machine, a Cylinder papermaking machine, an Inclined papermaking machine, a Twin Wire papermaking machine, and combination papermaking machines formed by combining the same or different types of papermaking machines selected from these.

[0044] In the papermaking process, it is preferable to dehydrate the wet sheet so that the water retention of the wet sheet obtained, i.e., the moisture content of the wet sheet, is 65 to 75 mass% relative to the total mass of the wet sheet. If the water retention of the wet sheet is equal to or higher than the lower limit, the hot water-soluble resin can be sufficiently dissolved in the drying process described below, making it possible to develop strength. If the water retention of the wet sheet is equal to or lower than the upper limit, wire peeling problems caused by insufficient strength of the wet sheet due to excess moisture can be prevented. The water retention rate of the wet sheet can be controlled by suction, water retention due to the degree of fibrillation of the organic natural fibers, or the amount of organic natural fibers added. Specifically, the water retention rate of the wet sheet tends to increase when the dehydration of the wet sheet is weakened, the degree of fibrillation of the organic natural fibers is increased, or the amount of organic natural fibers added is increased, whereas the water retention rate of the wet sheet tends to decrease when the dehydration of the wet sheet is strengthened, the degree of fibrillation of the organic natural fibers is decreased, or the amount of organic natural fibers added is decreased.

[0045] (Compression process) The compression step is a step of compressing the wet sheet to a compression ratio of 0 to 45% to obtain a compressed sheet. The compression ratio is 0 to 45%, preferably 15 to 35%. If the compression ratio is equal to or greater than the lower limit, the extremely large gaps formed between the fibers can be reduced, and the homogeneity can be improved. When the adsorption sheet is used for a desiccant rotor, the thickness of the moisture-absorbing sheet may be limited in order to reduce the pressure loss of the honeycomb filter material incorporated in the desiccant rotor during ventilation. In such a case, the compression ratio can be controlled so that the thickness of the sheet after drying becomes smaller. If the compression ratio is equal to or less than the upper limit, the thickness of the sheet after drying can be controlled so that the thickness of the sheet after drying becomes larger. The compression ratio can be controlled by adjusting the pressure during compression, and the higher the pressure, the higher the compression ratio tends to be. The pressure during compression is not particularly limited, but is preferably 0 to 0.4 MPa. The compression ratio is calculated by the following formula (1). Compressibility (%) = {(thickness of wet sheet before compression - thickness of wet sheet after compression) / thickness of wet sheet before compression} × 100 (1) The "thickness of the wet sheet after compression" refers to the thickness of the compressed sheet.

[0046] The wet sheet is also dehydrated in the compression step. The moisture retention of the compressed sheet, i.e., the moisture content of the compressed sheet, is preferably 55 to 70 mass % relative to the total mass of the compressed sheet, and more preferably 60 to 65 mass %. If the moisture retention of the compressed sheet is equal to or higher than the lower limit, the hot water-soluble resin can be sufficiently dissolved in the drying step described below, allowing the sheet to exhibit strength. If the moisture retention of the compressed sheet is equal to or lower than the upper limit, reduction in strength due to surface roughness caused by boiling can be prevented in the drying step. The water retention of the compressed sheet can be controlled by adjusting the pressure during compression, and the higher the pressure, the lower the water retention tends to be.

[0047] (drying process) The drying step is a step in which the compressed sheet is dried to dissolve the hot water soluble resin and adhere it to the organic natural fibers to obtain an adsorption sheet. Examples of drying methods for the compressed sheet include drying methods using a Yankee dryer, a rotary dryer, a hand dryer, an air dryer, a cylinder dryer, a suction drum dryer, an infrared dryer, etc. Among these, contact dryers such as a Yankee dryer are particularly preferred. In the case of a hot air non-contact dryer, depending on the air volume and temperature, moisture in the compressed sheet may be lost during drying before it becomes hot water, causing the hot water-soluble resin to not dissolve sufficiently, resulting in insufficient strength development. The drying temperature of the compressed sheet is a temperature at which the moisture in the compressed sheet becomes hot water at a temperature at which the hot water soluble resin starts to dissolve, i.e., hot water of 60°C or higher, and may be determined according to the type of hot water soluble resin. For example, when PVA is used as the hot water soluble resin, the drying temperature of the contact dryer is preferably 70 to 180°C, more preferably 120 to 140°C. When EVOH is used as the hot water soluble resin, the drying temperature is preferably 110 to 150°C, more preferably 125 to 140°C. When starch is used as the hot water soluble resin, the drying temperature is preferably 70 to 180°C, more preferably 100 to 140°C. If the drying temperature is equal to or higher than the lower limit, the moisture in the compressed sheet becomes hot water at a temperature at which the hot water soluble resin starts to dissolve. If the drying temperature is equal to or lower than the upper limit, discoloration due to overheating, adhesion to the canvas due to dry heat fusion, and transfer failure can be prevented in cases where these may occur.

[0048] The hot water-soluble resin in the compressed sheet before drying maintains its fibrous, granular, or other shape. However, when the compressed sheet is dried at a specified temperature, the moisture in the compressed sheet becomes hot water of 60°C or higher, and the hot water-soluble resin dissolves and adheres to the organic natural fibers. The adsorption sheet obtained in the drying step is wound up on a roll or the like as necessary.

[0049] <Action and effect> In the adsorption sheet of the present invention described above, before drying, the surface of the organic fiber mainly composed of three components, synthetic fiber, hot water soluble resin, and organic natural fiber, becomes the surface of the organic fiber mainly composed of two components, organic natural fiber with hot water soluble resin attached and synthetic fiber, after drying, and the organic surface area is small compared to the weight ratio of the organic material blended. When the adsorption sheet burns, flammable gas is generated from the organic surface, so it is considered that the smaller the organic surface area is, the less instantaneous flammable gas is generated and the higher the flame retardant effect is. In other words, the adsorption sheet of the present invention, which has a small organic surface area compared to the organic weight, is considered to have excellent flame retardancy. Moreover, since the adsorption sheet of the present invention has excellent flame retardancy, there is no need to excessively increase the proportion of inorganic material, and since the proportion of organic material is sufficient, it is also excellent in processability. As described above, the adsorbent sheet of the present invention has excellent flame retardancy and processability, and is therefore suitable as an adsorbent sheet for a desiccant rotor. EXAMPLES

[0050] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these. Various measurements and evaluations were carried out by the following methods.

[0051] "Measurement and Evaluation" <Flame retardancy evaluation> The adsorption sheet was cut into a strip 13 mm wide and 13 cm long to prepare a test piece. The height of the flame of a commercially available portable lighter was adjusted to 20 mm, and the upper half (10 mm) of the flame was applied to the lower end of the test piece in the longitudinal direction in air for 10 seconds to perform a combustion test. After the combustion test, the burned part of the test piece was visually observed, and the flame retardancy was evaluated according to the following evaluation criteria. "Good" and "Good" are considered to be acceptable. 〇: The burning area reaches less than 5cm from the bottom end. △: The burning part reaches more than 5cm and less than 10cm from the bottom end. ×: The burning area reaches more than 10 cm from the bottom end.

[0052] <Evaluation of processability> The adsorption sheet was passed between the meshing rack gear and pinion gear with a pitch of 3 mm to process it into a corrugated shape. The gear temperature was set to an optimal temperature between 150 and 190°C depending on the type of hot water soluble resin and organic natural fiber contained in the adsorption sheet. The state of the adsorption sheet after processing was visually observed, and the processability was evaluated according to the following evaluation criteria. "Good" and "Good" were considered to be acceptable. ◯: The corrugated shape is well maintained. △: Slight deformation of the corrugated shape is observed. ×: The deformation of the corrugated shape is clearly observed.

[0053] <Overall rating> The overall evaluation was based on the results of flame retardancy and processability and was performed according to the following criteria. ◎: When all results are “O”. ○: Only ○ and ○ are included, not including ×. ×: If it contains even one "×".

[0054] "Example 1" Glass fiber (manufactured by U.G. Base Materials Co., Ltd., product name "ECE06", average fiber length 6 mm, average fiber diameter 6.5 μm) as inorganic fiber, PVA fiber (manufactured by Kuraray Co., Ltd., product name "VPB105-1", average fiber length 3 mm, average fiber diameter 10.5 μm) as fibrous hot water soluble resin, and PET fiber (manufactured by Teijin Limited, product name "TJ04CN", average fiber length 5 mm, average fiber diameter 12.5 μm) as synthetic fiber were disintegrated and dispersed in water so that the content of each material in the adsorption sheet was the value shown in Table 1, to obtain a first dispersion with a moisture content of 99.6 mass%. Separately, A-type silica gel as an inorganic adsorbent, wood pulp (coniferous pulp, average fiber length 2.1 mm, average fiber width 25 μm) as an organic natural fiber, potassium titanate fiber (average fiber length 15 μm, average fiber diameter 0.4 μm) as a support aid, and citric acid (manufactured by COFCO Biochemical (AnHui) Co., Ltd.) as an acid were added to water and stirred and mixed, and then anionic polyacrylamide (manufactured by Kurita Water Industries Ltd., product name "High Holder C503") was added as a polymer flocculant to flocculate the inorganic adsorbent, organic natural fiber, and support aid, and a second dispersion with a moisture content of 97.0% by mass was obtained. The amount of acid added was 5.5 parts by mass with respect to a total of 100 parts by mass of the inorganic adsorbent, organic natural fiber, and support aid, and the amount of polymer flocculant added was 0.3 parts by mass with respect to a total of 100 parts by mass of the inorganic adsorbent, organic natural fiber, and support aid. The first dispersion and the second dispersion were mixed in a mass ratio of 27:1 to obtain a papermaking slurry having a water content of 99.94 mass %. The slurry was made into a paper using an inclined wire type paper machine while adjusting the wire retention to 90% or more, and a wet sheet with a water retention of 65% by mass was obtained. The obtained wet sheet was compressed with a press roll so that the compression ratio was 35%, to obtain a compressed sheet with a moisture content of 55% by mass. The pressure during compression was set to 0.4 MPa. The compressed sheet was dried at 140° C. using a Yankee dryer to dissolve the hot water-soluble resin, thereby obtaining an adsorption sheet having a thickness of 160 μm in which the hot water-soluble resin was attached to the organic natural fibers. The resulting adsorption sheet was evaluated for flame retardancy and processability, and the results are shown in Table 1.

[0055] "Examples 2 to 11, Comparative Examples 1 to 3, 5, and 7" Adsorption sheets were produced in the same manner as in Example 1, except that the type of each material and the content in the adsorption sheet were changed as shown in Tables 1 to 3, and the flame retardancy and processability were evaluated. The results are shown in Tables 1 to 3. In Example 6, rock wool (Lapinus Co., Ltd., product name "Lapinus RS470-T", average fiber length 650 μm, average fiber diameter about 9 μm) was used as the inorganic fiber. In Example 7, molecular sieve (synthetic zeolite) (Union Showa Co., Ltd., product name "Molecular Sieve 13X") was used as the inorganic adsorbent. In Example 8, PE fiber (Mitsui Chemicals, Inc., product name "SWP·EST2", average fiber length 0.9 mm, average fiber diameter about 10 μm) was used as the synthetic fiber. In Example 9, straw pulp (average fiber length 0.6 mm, average fiber diameter 10 μm) was used as the organic natural fiber. In Example 10, EVOH fiber (Kuraray Co., Ltd., product name "S-030", average fiber length 5 mm, average fiber diameter about 8 μm) was used as the hot water soluble resin.

[0056] "Comparative Example 4" Except for changing the type of each material and the content in the adsorbent sheet as shown in Table 3 and changing the amount of polymer flocculant added to 1.0 part by mass per 100 parts by mass of the inorganic adsorbent, organic natural fiber, and supporting aid, an adsorbent sheet was manufactured in the same manner as in Example 1, and the flame retardancy and processability were evaluated. The results are shown in Table 3.

[0057] "Comparative Example 6" An attempt was made to manufacture an adsorbent sheet in the same manner as in Example 1, except that the type of each material and its content in the adsorbent sheet were changed as shown in Table 3, and the amount of polymer flocculant added was changed to 1.0 part by mass per 100 parts by mass of the total of the inorganic adsorbent, organic natural fiber, and support aid. However, since it was not possible to form the sheet, the flame retardancy and processability could not be evaluated.

[0058] [Table 1]

[0059] [Table 2]

[0060] [Table 3]

[0061] As is clear from the results in Tables 1 to 3, the adsorption sheets obtained in the respective Examples were excellent in flame retardancy and processability. In contrast, the adsorption sheets obtained in the respective comparative examples were inferior in either flame retardancy or processability. Specifically, the adsorption sheets of Comparative Examples 1 and 2, in which the content of inorganic matter was less than 84% by mass, were poor in flame retardancy. The adsorption sheet of Comparative Example 3, which did not contain a hot water-soluble resin, was poor in flame retardancy. The adsorption sheet of Comparative Example 4, which did not contain organic natural fibers, was poor in processability. In the case of Comparative Example 4, since organic natural fibers, which are carriers for supporting the inorganic adsorbent, were not used, it was necessary to strengthen the aggregation by increasing the amount of polymer flocculant added compared to Example 1 in order to ensure wire retention. As a result, the aggregated flocs (aggregates) became too large, the texture deteriorated, and the appearance became non-uniform. The adsorption sheet of Comparative Example 5, which did not contain synthetic fibers, was poor in processability. In the case of Comparative Example 6, in which no inorganic fibers were used, in order to ensure wire retention, it was necessary to further strengthen the aggregation by increasing the amount of polymer flocculant added compared to Comparative Example 4. As a result, the aggregated flocks (aggregates) became even larger than in Comparative Example 4, and could not be formed into sheets. The adsorption sheet of Comparative Example 7, in which the content of inorganic matter was more than 92 mass %, was poor in processability.

Claims

1. An adsorption sheet containing inorganic fibers (excluding the supporting aid described below), an inorganic adsorbent (excluding the supporting aid described below), synthetic fibers (excluding the supporting aid described below), organic natural fibers (excluding the supporting aid described below), a hot water soluble resin (excluding the supporting aid described below), and a supporting aid, the inorganic adsorbent is at least one selected from the group consisting of A-type silica gel, B-type silica gel, zeolite, activated carbon, and clay; The hot water-soluble resin is a resin that begins to dissolve in hot water of 60° C. or higher, the hot water soluble resin is attached to the organic natural fiber, The support aid is a fine fiber having an average fiber length of 20 μm or less, The adsorption sheet has a content of the inorganic adsorbent of 40 to 75 mass %, a content of the organic matter contained in the adsorption sheet of 8 to 16 mass %, and a content of the inorganic matter contained in the adsorption sheet of 84 to 92 mass %, relative to the total mass of the adsorption sheet.

2. The adsorption sheet according to claim 1 , wherein the inorganic fibers are glass fibers.

3. 3. The adsorption sheet according to claim 1, wherein the synthetic fibers are at least one of polyethylene terephthalate fibers and polyolefin fibers.

4. The adsorption sheet according to any one of claims 1 to 3, wherein the organic natural fiber is at least one of wood pulp and straw pulp.

5. The adsorption sheet according to any one of claims 1 to 4, wherein the content of organic matter contained in the adsorption sheet is 10 to 14 mass% and the content of inorganic matter contained in the adsorption sheet is 86 to 90 mass% relative to the total mass of the adsorption sheet.

6. The adsorption sheet according to any one of claims 1 to 5, which is for a desiccant rotor.

7. 7. The adsorbent sheet according to claim 6, wherein the inorganic adsorbent is at least one of type A silica gel and zeolite.

8. A method for producing the adsorption sheet according to any one of claims 1 to 7, a step of disintegrating and dispersing the inorganic fibers, the synthetic fibers, and the hot water-soluble resin in water to obtain a first dispersion; dispersing the remaining material in water to obtain a second dispersion; mixing the first dispersion with the second dispersion to obtain a papermaking slurry; A step of producing the slurry using a papermaking machine to obtain a wet sheet having a water retention rate of 65 to 75% by mass; compressing the wet sheet to a compression rate of 0 to 45% to obtain a compressed sheet; and drying the compressed sheet to dissolve the hot water soluble resin and adhere it to the organic natural fibers.

9. The method for producing an adsorbent sheet according to claim 8, wherein the compressed sheet is dried at 70 to 180°C.

Citation Information

Patent Citations

  • Heat resistant adsorption sheet and its production

    JP1997094422A

  • Adsorption element and manufacturing method therefor

    JP2002239329A

  • Adsorption sheet, adsorption elements and adsorption treatment apparatus

    JP2004249259A

  • Sheet-like article for dehumidification and filter material for dehumidification

    JP2009240935A

  • Sheet-like material for dehumidification

    JP2012192393A